2011
DOI: 10.3928/01477447-20110826-11
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography as a Diagnostic Tool in Assessing Deltoid Ligament Injury in Supination External Rotation Fractures of the Ankle

Abstract: The medial deltoid ligament is the primary stabilizing structure in the ankle joint following lateral malleolar fracture. However, medial deltoid ligament ruptures are difficult to diagnose using current imaging modalities. We hypothesized that ultrasonography can be used to accurately allow early clinical assessment of ankle fracture stability, thereby negating the need to perform plain film stress views of the acutely injured ankle. This prospective study included 12 patients (age range, 18-72) with supinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 22 publications
2
40
0
4
Order By: Relevance
“…Ultrasound has greater diagnostic ability with a 100 % sensitivity and specificity in this study [36]. Other views should be guided by the clinical examination, such as high fibular pain.…”
Section: Imagingmentioning
confidence: 65%
“…Ultrasound has greater diagnostic ability with a 100 % sensitivity and specificity in this study [36]. Other views should be guided by the clinical examination, such as high fibular pain.…”
Section: Imagingmentioning
confidence: 65%
“…In the setting of Weber type B and C fractures, US was found to have 100% sensitivity for the detection of complete rupture of the deltoid ligament but only sensitivity of 50% for partial ruptures; thus, it may be helpful but not entirely replace MRI for the assessment of medial instability in this clinical setting . Another study demonstrated 100% sensitivity and specificity of US for medial deltoid rupture with a 100% correlation between US and arthroscopy in supination external rotation fractures of the ankle, thus possibly obviating the need for stress radiographs …”
Section: Medial Collateral Ligament (Deltoid) Complexmentioning
confidence: 99%
“…23 Another study demonstrated 100% sensitivity and specificity of US for medial deltoid rupture with a 100% correlation between US and arthroscopy in supination external rotation fractures of the ankle, thus possibly obviating the need for stress radiographs. 24…”
Section: Medial Collateral Ligament (Deltoid) Complexmentioning
confidence: 99%
“…So kann z. B. bei der Distorsion des oberen Sprunggelenks, welche mit 5% eine der häufigs-ten Verletzungen in der chirurgischen Notaufnahme darstellt [15], die Ruptur des medialen [6] und lateralen Kollateralbandapparats [11,13] …”
Section: Sonografieunclassified